Reuse of eggshell waste and recycled glass in the fabrication porous glass-ceramics - Saparuddin, Dur Iffa; Mohd Zaid, Mohd Hafiz; Hj Ab Aziz, Sidek; Matori, Khamirul Amin (MDPI AGmembranes@mdpi.com, 2020)
This study was conducted to fabricate and characterize of glass–ceramic foam derived from soda-lime silica (SLS) glass waste and eggshell (ES) waste as a foaming agent by using empirical formula [ES] × [SLS]100−x where x = 1 wt%, 3 wt%, 6 wt%, 9 wt%. The samples undergo a heat-treatment process at temperature 800 °C with a heating rate of 10 °C/min. The properties of the samples were measured by average density measurement and linear expansion. The structural properties were studied by XRD, FESEM and FTIR concerning the different composition of the foaming agent while the mechanical properties were determined by compressive strength using UTM. The lowest density and compressive strength were achieved by 0.326 g/cm3 and 0.04 MPa, respectively with the highest linear expansion at 77.33% by the addition of 3 wt% of ES. Moreover, the cristobalite phase (SiO2) were identified after the heat treatment process. The production of foam glass–ceramics using SLS glass and ES can be applied to prepare different type of porosity that gives benefit to the environment and energy usage.